KOMPETENSI SUMBER DAYA MANUSIA DAN PERAN AUDIT INTERNAL SEBAGAI FAKTOR PENENTU KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN WONOSOBO - Rayi Hidayati; Hayu Wikan Kinasih (Universitas Dian Nuswantoro, 2023)
This study was conducted to analyze the Competence of Human Resources and the Role of Internal Audit in relation to the determination of the Quality of Financial Statements of the Regional Government of Wonosobo District. The object of this research is the financial management section of the OPD of Wonosobo District. The number of respondents in this study were obtained 51 respondents from 43 Regional Apparatus Organizations (OPD) in Wonosobo Regency. The analysis technique used to analyze the relationship between variables in this study is multiple linear regression analysis. The results of the research showed that Human Resources Competencies and The Role of Internal Audit are able to explain the variable of the quality of Local Government Financial Statements of Wonosobo District as much as 58.1%, with the result that the two independent variables are positively and significantly effect on the quality of Local Government Financial Statements of Wonosobo District